Unpacking the Role of Brand Advocacy and Para-Social Relationships in Shaping Brand Trust on Social Media - Jiang, Jiarui; Hashim , Sharizal (Journal of Ecohumanism, 2025)
This study investigates the impact of various factors in influencer marketing on brand performance when influencers endorse or collaborate with brands. Specifically, it examines the influence of quasi-social relationships, influencer attractiveness, influencer credibility, and endorsement content quality on brand trust, as well as the role of brand trust in brand promotion. The study is grounded in the stimulus-organism response hypothesis and encompasses a survey involving 333 participants. The results demonstrate that influencers’ credibility significantly influences consumers’ trust in brands, subsequently impacting brand publicity. These findings hold significant managerial implications and can assist decision-makers in selecting optimal marketing strategies. The findings show para-social ties often fails to enhance brand trust. Besides managers can use attractive influencers to craft visually appealing endorsements. To enhance brand trusts, managers need to collaborate with credible influencers with stronger reputation. Simultaneously, manager must ensure high quality and relevant content to enhance consumer trust.